The Effect of Erector Spinae Block versus Serratus Plane Block on Pain Scores and Diaphragmatic Excursion in Multiple Rib Fractures. A Prospective Randomized Trial - El Malla, Dina Ahmed; Helal, Rehab Abd El fattah; Zidan, Tamer Atef Mohamed; El Mourad, Mona Blough (Pain medicine (Malden, Mass.), 2022)
Abstract Objectives We aimed to investigate whether ultrasound guided erector spinae plane block and serratus anterior plane block would provide effective and safe analgesia in patients with fracture ribs, and to detect their effects on diaphragmatic excursion in such cases. Design Prospective double-blind randomized study Settings Tanta University Hospitals Subject Fifty adult patients ASA I, II with fracture ribs. Methods Patients were randomized to receive either ultrasound guided erector spinae block (Group I) or serratus plane block (Group II) with injection of 19 ml bupivacaine 0.25% plus 1 ml dexamethasone (4 mg). Pain scores, 24 hour total analgesic requirements, diaphragmatic excursion and incidence of adverse events were recorded. Results At rest and dynamic pain scores were significantly lower in Group I as compared to Group II from 2 hour up to 24 hour post block [median differences (95% CI): −1 (−0.9999; 0.0002), −1 (−0.9999; 0.0002), −1 (−0.9998; 0.0003), −1(−1.000;−0.000) and −1(−2.0000;−1.0000), −1(−0.9998;−0.0001), −1(−1.0001;−1.0002), −1(−2.000; 0.000), respectively], with a significant reduction in 24 hour opioid consumption in Group I in comparison to Group II (P = .004*). Diaphragmatic excursion showed a significant improvement in Group I when compared to Group II at 2, 6, 12, and 24 hour after the block (P = .024*, .038*, .027*, .042* correspondingly). No adverse events were noted. Conclusions Both erector spinae block and serratus plane block provided safe and effective pain relief in traumatic rib fractures. Although the erector spinae group displayed significantly reduced pain scores, decreased analgesic needs and improved diaphragmatic excursion as compared to serratus group, nevertheless, this was of no clinical significance.